FIGO consensus guidelines on placenta accreta spectrum disorders: Prenatal diagnosis and screening - Jauniaux, E; Bhide, A; Kennedy, A; Woodward, P; Hubinont, C; Collins, S (Wiley, 2018)
Recent population studies have shown that placenta accreta spectrum (PAS) disorders remain undiagnosed before delivery in half to two-thirds of cases. In a series from specialist diagnostic units in the USA, around one-third of cases of PAS disorders were not diagnosed during pregnancy. Maternal mortality and morbidity are reduced when women with PAS disorders, particularly the invasive forms—placenta increta or percreta—deliver in a center of excellence by a multidisciplinary care team with experience in managing the surgical risks and perioperative challenges presented by these disorders. Transfer to a center of excellence, however, relies on both recognition of the women at risk of PAS disorders and on accurate prenatal diagnosis. Current prenatal diagnosis rests on subjective interpretation of “typical” sonographic findings or signs with two-dimensional (2D) grey-scale and color Doppler imaging. Many signs have been reported in the literature with varying descriptions as to their sensitivity and specificity. The published literature is difficult to interpret because of several problems in the definition, terminology, and diagnosis of this disorder. To improve consistency and allow appropriate comparison of different imaging markers, panels of experts have published consensus statements that aim to standardize the descriptions and minimum requirements for an ultrasound scan to diagnose PAS disorders. Magnetic resonance imaging (MRI), although widely employed, has yet to clearly demonstrate a significant improvement in management or pregnancy outcomes. MRI is expensive and requires expertise that is rarely available in most low-income countries and many medium-income countries. MRI is currently only recommended as an adjunct to ultrasound imaging by many professional bodies throughout the world including the Royal College of Obstetricians and Gynaecologists (RCOG) in the UK. Irrespective of the imaging modality used, prenatal diagnosis of PAS disorders remains subjective, with accuracy depending on the experience of the operator, which has so far been limited by the rarity of the condition and the lack of training programs similar to those existing for the screening of fetal aneuploidies and fetal anatomical defects, such as congenital heart defects. PAS disorders are a growing obstetric issue and with the continuous increase in cesarean deliveries more studies are being published yearly. The definitive diagnosis, however, can only be made clinically at delivery and should be confirmed by histopathology wherever possible. This chapter reviews the various prenatal diagnostic techniques described in the international literature for the diagnosis of PAS disorders. As abnormal placentation is a spectrum disorder including both abnormal adherence (placenta creta) and abnormal invasion (placenta increta and placenta percreta), the term PAS disorders is used here as the overarching descriptor of the whole condition.